Zur praktischen Bedeutung des neuen japanischen Gesellschaftsrechts für ausländische Investoren - Westhoff, Jörn (Zeitschrift für Japanisches Recht, 2006)
This article undertakes to outline the newly revised Japanese corporate legislation’s practical importance for foreign investors, with a special focus on the corporate governance of Japanese stock corporations. Few of the new regulations require immediate attention from existing stock corporations, but the new legislation provides for more flexibility in general, such as abolition of the minimum capital requirement, flexibility in payment of dividends, or the option to replace the board of directors with a single director. The author shows, however, that in joint-venture corporations or other foreign-affiliated companies, the old system served the needs of foreign mother companies very well, while the new regulations do not necessarily provide major advantages. Additionally, the author gives some hints on why the newly introduced LLC and LLP may provide interesting alternatives at the start of an enterprise in Japan.